Sustainable Supply Chain Management - Practical Ideas for Moving Towards Best Practice - Cetinkaya, B; Cuthbertson, R; Ewer, G; Klaas-Wissing, T; Piotrowicz, W; Tyssen, C (Springer, 2011)
This book focuses on the need to develop sustainable supply chains - economically, environmentally and socially.This book is not about a wish list of impractical choices, but the reality of decisions faced by all those involved in supply chain management today.Our definition of sustainable supply chains is not restricted to so-called "green" supply chains, but recognises that in order to be truly sustainable, supply chains must operate within a realistic financial structure, as well as contribute value to our society. Supply chains are not sustainable unless they are realistically funded and valued. Thus, a real definition of sustainable supply chain management must take account of all relevant economic, social and environmental issues.This book contains examples from a wide range of real-life case studies, and synthesizes the learnings from these many different situations to provide the fundamental building blocks at the centre of successful logistics and supply chain management.